Water governance in Brazil: What is the role of city governments? - Nicollier, Valérie; Kiperstok, Asher; Bernardes, Marcos Eduardo Cordeiro (Estudos Avançados, 2023)
This article discusses the role of municipalities in Brazil’s National Water Resources Management System (Singreh) in light of water governance. Municipalities have a weak participation in this system and, as a rule, do not have a municipal water resources policy. Supported by indicators proposed by the Organization for Economic Cooperation and Development (OECD) and the Observatório das Águas do Brasil (OGA), the “failure of the municipality” in water governance in Brazil is identified. The current legal reforms that affect water resources tend to further weaken the role of municipalities in Singreh. The urgency and feasibility of water governance within the municipalities is highlighted, as a mechanism to promote the integrated and participatory water resources management.